Physiological effects of prenatal ultrasound exposure on bone-related development of young rabbits / Iza Nurzawani Che Isa - Che Isa, Iza Nurzawani (Institute of Graduate Studies, UiTM, 2017)
Prenatal ultrasound examination is routinely carried out on most pregnant women since it is considered to be safe. The procedure is however often exploited for social and business interest rather than for medical diagnosis. Despite this procedure having an excellent safety record, ultrasound imaging tends to evoke temperature increase due to heat absorption from prolonged ultrasound beams and leads to intrauterine hyperthermia. This ex-vivo experimental study was conducted to examine bone-related physiological changes of young rabbits exposed prenatally to ultrasound. Oryctolagus cuniculus were time-mated and assigned into control and experimental groups. The control group was allowed to have a full term delivery without any exposure to ultrasound. Each pregnant doe in the experimental group received a single exposure to ultrasound during the applicable gestational stage of the group to which it was assigned. The exposure lasted 30 min, 60 min, and 90 min at 1st, 2nd and 3rd stage, accordingly. For each exposure, the working frequency used was 5.76 MHz, and the mechanical (MI) and thermal indices (TI) recorded were 1.0 and 0.2, respectively.